1982
DOI: 10.1002/aja.1001630302
|View full text |Cite
|
Sign up to set email alerts
|

Functional morphology of lingual protrusion in marine toads (Bufo marinus)

Abstract: Bufo marinus catches its prey by stiffening the intrinsic muscles of the tongue, rapidly flipping the tongue out of the mouth. High-speed cinematography synchronized with computer-analyzed electromyograms (EMGs)shows that during the flip the tongue is supported by the M. genioglossus medialis and that this muscle stiffens into a rod when stimulated. Coincident stiffening of the transversely arranged M. genioglossus basalis provides a wedge under the anterior tip of this rod. Stiffening of the M. submentalis de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
48
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 20 publications
(14 reference statements)
5
48
0
Order By: Relevance
“…In anurans the mentomeckelian is among the last bones to appear at metamorphosis (see review by Trueb, 1985). The mentomeckelian remains discrete in most anuran taxa, where movement of these paired bones aids both in depressing the symphysis during protrusion of the tongue for feeding (Gans & Gorniak, 1982) and in closing the external nares during respiration (Gans & Pyles, 1983). The absence of an ossified mentomeckelian in some pipoids is derived within anurans and is associated with modifications to the tongue ( W e b & Cannatella, 1982).…”
mentioning
confidence: 99%
“…In anurans the mentomeckelian is among the last bones to appear at metamorphosis (see review by Trueb, 1985). The mentomeckelian remains discrete in most anuran taxa, where movement of these paired bones aids both in depressing the symphysis during protrusion of the tongue for feeding (Gans & Gorniak, 1982) and in closing the external nares during respiration (Gans & Pyles, 1983). The absence of an ossified mentomeckelian in some pipoids is derived within anurans and is associated with modifications to the tongue ( W e b & Cannatella, 1982).…”
mentioning
confidence: 99%
“…However, its contribution to the prey-catching behavior is more complex as the activity level of muscle contraction is changing continuously during the execution of tongue prehension behavior (Gans and Gorniak, 1982). High-speed cinematography synchronized with computeranalyzed electromyograms (EMGs) revealed that the first peak of the contraction in depressor mandibulae muscle appeared in the preparatory phase of prey-catching behavior prior to mouth opening when the activity level of muscle fluctuated between 10 and 100% (Gans and Gorniak, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In later phase of retraction the activity of depressor mandibulae drops and then becomes silent before the tongue reaches the back of the oral cavity. Taking into consideration the very quick time course of prey-catching behavior (Gans and Gorniak, 1982), we supposed that feedback and feedforward modulations of rapidly changing activity of the depressor mandibulae muscle could be provided via the monosynaptic sensory input transported by the trigeminal nerve to the facial motoneurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many organisms, however, exploit prey in both aquatic and terrestrial environments. Such versatility in feeding behaviour can exist concomitantly with discrete metamorphic stages (Gans & Gorniak 1982, Nishikawa & Cannatella 1991, Reilly 1996, or within a single life-history stage (Summers et al 1998, Deban & Marks 2002, Luiselli et al 2002. Few kinematic and behavioural studies have focused specifically on fishes that feed in both aquatic and aerial environments during the same life history stage (Hyatt 1971, Zahl et al 1977, Seghers 1978, Sponder & Lauder 1981.…”
Section: Introductionmentioning
confidence: 99%